Depression and Associated Factors in Chinese Patients With Chronic Kidney Disease Without Dialysis: A Cross-Sectional Study - Duan, Difei; Yang, Lin; Zhang, Min; Song, Xiaoli; Ren, Wen (Frontiers in Public Health, 2021)
Background: Chronic kidney disease (CKD) has been a globally public health problem over the past decades. The maintenance of physical and mental health is of importance for patients nowadays. Notably, depression is prevalent and associated with various adverse events in CKD patients without dialysis. Prior studies have reported that pain, negative illness perception, pain, and low self-esteem are potential risk factors of depression, while few studies have comprehensively investigated the mechanisms among these factors and depression among this population. Purpose: This study aims to investigate the prevalence of depression and further explore the risk factors and mechanisms of depression among CKD patients without dialysis in China. Design and Methods: We conducted a cross-sectional study in patients with diagnosed CKD to investigate the prevalence of depression was by the Beck Depression Inventory-II (BDI-II). The data on pain interference, illness perception, and self-esteem were also collected via self-administered questionnaires. A structural equation model (SEM) was used to examine the factors associated with depression. Main findings: From June to October 2019, we successfully interviewed 334 CKD patients at the outpatient clinics. Their mean age was 45.6 years (ranging from 19 to 74 years), and 48.5% were male. Most respondents were at early CKD stages (77.5% stage 1-3) and the prevalence of depression was 22.2%. We found that illness perception had a strong effect on depression, either directly or indirectly via the modification of self-esteem. Similar findings were found in pain interference, but weaker associations found. Conclusion and recommendations: Negative illness perception, low self-esteem and severe pain interference were the risk factors for depression among Chinese CKD patients without dialysis. Future studies are warranted to formulate the intervention strategies for these high-risk populations.